QUALITY IN MEDICINEAdherence to antihypertensive therapy among heart transplant recipients - Wasilewski, Grzegorz Jan; Milaniak, Irena; Janik, Łukasz; Sadowski, Jerzy; Przybyłowski, Piotr (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2014)
Introduction: Adherence to therapeutic recommendations, concerning in particular drug administration, diet and healthy life style, is essential to obtain optimal medical treatment effects. Elevated blood pressure is an extremely important risk factor for cardiovascular diseases such as coronary artery disease, chronic heart failure and stroke, as well as chronic kidney disease. Aim: The aim of the study was to assess the level of adherence among heart transplant recipients and to explain the reasons for non-adherence phenomenon. Material and methods The study was performed on 55 heart allograft recipients: 11 women (20%) and 44 men (80%), all hypertensive. Participation in the study was voluntary and the three-part questionnaire was anonymous to obtain reliable answers. The second part was designed using the Modified Morisky Scale (MMS) consisting of questions assessing motivation and knowledge among patients. The third included questions concerning lifestyle, reasons for non-adherence and methods to improve it. Results : In self-assessment of the adherence to medical recommendations on a scale of 0 to 10 the analyzed population estimated their level of adherence to be on average 8.49 (± 1.33), which is a considerably high result. It was discovered that both the level of motivation (2.20) and knowledge (2.83) are high among heart transplant recipients. Still, the level of knowledge was significantly higher than the motivation (p < 0.005). Correlation analysis revealed that the self-assessed adherence level correlated positively with the level of motivation (r = 0.357; p < 0.007). Conclusions: Creation of an active attitude of the patient in the process of treatment is a crucial and at the same time often difficult task demanding cooperation of the patient, the patient’s close family and the whole therapeutic team.